2022
DOI: 10.1186/s12891-022-05148-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kinesio taping on skin deformation during knee flexion and extension: a preliminary study

Abstract: Background Kinesio Taping (KT) is proved useful to many musculoskeletal disorders. But the mechanism remains unclear. The kinesio tape works by sticking to the skin surface. So exploring the interaction between the tape and the skin and analyzing its biomechanical influence may be an effective way to explore the mechanism of the tape. Objectives This study aimed to investigate the effect of Kinesio taping and taping methods on skin deformation duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It is unlikely that any direct mechanical benefit to the joint would result from elastic tape applied with little tension; hence, there may be a neuromuscular effect or increased sensory input around the joint, which may stimulate cutaneous and muscle mechanoreceptors by stretching the skin during motion ( 43 ). The experimental tape encompassed the shoulder joint more completely, and, theoretically, this may have caused more biomechanical skin deformation, particularly during internal and ER motions ( 44 ). Furthermore, studies examining the ankle plantar flexors have shown that K-Tape may affect muscle activity, as seen in one study analyzing the EMG activity during a vertical jump ( 45 ) and in other studies showing an effect on the H-reflex ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that any direct mechanical benefit to the joint would result from elastic tape applied with little tension; hence, there may be a neuromuscular effect or increased sensory input around the joint, which may stimulate cutaneous and muscle mechanoreceptors by stretching the skin during motion ( 43 ). The experimental tape encompassed the shoulder joint more completely, and, theoretically, this may have caused more biomechanical skin deformation, particularly during internal and ER motions ( 44 ). Furthermore, studies examining the ankle plantar flexors have shown that K-Tape may affect muscle activity, as seen in one study analyzing the EMG activity during a vertical jump ( 45 ) and in other studies showing an effect on the H-reflex ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 9, 2024. ; https://doi.org/10.1101/2024.03.07.24303944 doi: medRxiv preprint biomechanics of the skin. [21,[28][29][30] Applying different tensions of it on the skin may reduce partial pressure, accelerate blood and lymphatic circulation, and increase muscle temperature, thus promoting regional microcirculation. [21,31,32] People with a psychologically anticipated response to the effect of KT are likely to induce greater placebo effects, thus contributing to enhanced muscle function.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…[27] These therapeutic effects are probably supported by the mechanisms of KT that it increases the subcutaneous space, stimulates skin sensory receptors, and provides support for mechanical behaviour and biomechanics of the skin. [21,[28][29][30] Applying different tensions of it on the skin may reduce partial pressure, accelerate blood and lymphatic circulation, and increase muscle temperature, thus promoting regional microcirculation. [21,31,32] People with a psychologically anticipated response to the effect of KT are likely to induce greater placebo effects, thus contributing to enhanced muscle function.…”
Section: Introductionmentioning
confidence: 99%